DA’WAH BI AL-HAL: MOSQUE-BASED RELIGIOUS TOURISM DESTINATION MANAGEMENT AT GREAT MOSQUE OF DEMAK - Kurnia Muhajarah (Kopertais Wilayah X Jawa Tengah, 2022)
Islam has left various important historical relics in the form of tombs, mosques, ex-kingdoms, customs and so on, that can be used as tourism potential. One of the tourism activities is in the form of mosque tourist destinations. As a formulation of the problem, what is the development of ODTW mosque management? How is the development of da'wah through mosque-based religious tourism? This writing uses a library research and it is qualitative by descriptive analysis. The results showed that the development of da'wah through mosque-based religious tourism had proceeded as expected. These could be seen, from the aspects of planning, organizing, actuating and controlling. From the aspect of planning, the planning of da'wah in the mosque has been well managed in accordance with management principles. The managers of mosques have well planned in the development of da'wah. Da'wah activities that will be carried out to achieve the objectives to be achieved effectively and efficiently have been realized as management guidelines. Likewise, when paying attention to the organizing system of da'wah developed by mosque managers, it can be said that the organization of da'wah has succeeded in attracting tourists and the growing development of Islamic syi'ar. Viewed from the aspect of organizing of da'wah that this problem has succeeded well. Judging from the aspects of da’wah’s controlling, this has been done by the managers and members of the mosque well and successfully. Even so, there are still some shortcomings, and these shortcomings must receive attention. Therefore, this research is expected to provide a solution to overcome the shortcomings of mosque tourism destinations in the tourism industry era.